Biofortification of wheat with zinc through zinc fertilization in seven countries - C. Q. Zou; Y. Q. Zhang; A. Rashid; H. Ram; E. Savasli; R. Z. Arisoy; I. Ortiz-Monasterio; S. Simunji; Z. H. Wang; V. Sohu; M. Hassan; Y. Kaya; et al. (Plant and Soil, 2012)

A 5′UTR SNP of GHRHR locus is associated with body weight and average daily gain in Chinese cattle - C. F. Zhang; H. Chen; Z. Y. Zhang; L. Z. Zhang; D. Y. Yang; Y. J. Qu; L. S. Hua; B. Zhang; S. R. Hu (Molecular Biology Reports, 2012)

An SNP in the MyoD1 Gene Intron 2 Associated with Growth and Carcass Traits in Three Duck Populations - Y. Wu; J. S. Pi; A. L. Pan; Y. J. Pu; J. P. Du; J. Shen; Z. H. Liang; J. R. Zhang (Biochemical Genetics, 2012)

The polymorphism analysis of CD169 and CD163 related with the risk of porcine reproductive and respiratory syndrome virus (PRRSV) infection - Y. W. Ren; Y. Y. Zhang; N. A. Affara; C. A. Sargent; L. G. Yang; J. L. Zhao; L. R. Fang; J. J. Wu; R. Fang; Q. Tong; J. Xiao; J. L. Li; et al. (Molecular Biology Reports, 2012)

Isolation and partial characterization of a new reovirus in the Chinese mitten crab, Eriocheir sinensis H Milne Edwards - S Zhang; J‐R Bonami (Journal of Fish Diseases, 2012)
A second type of freshwater crab reovirus has been isolated from Chinese mitten crab, Eriocheir sinensis H. Milne Edwards, in China; we named it E. sinensis reovirus ( Es RV816). The negatively stained virion is a non‐enveloped icosahedral particle, 60 ± 5 nm in diameter. Its genome is composed of 10 dsRNA linear pieces exhibiting an electrophoretic pattern of 5/3/2. The largest segment (RNA‐1) was cloned and sequenced. The deduced amino acid sequence, corresponding to the RdRp of the virus, showed 26% identity with the RdRp of Operophtera brumata (L.) cypovirus 19 in the genus Cypovirus and 24% identity with RdRp of Nilaparvata lugens (Stal) reovirus in the genus Fijivirus . On the basis of its ultrastructure and physicochemical properties, this virus is quite different from other crab reoviruses, and particularly with another freshwater crab reovirus Es RV905, recently classified in a new genus Cardoreovirus . This virus ( Es RV816) possesses all the characters of the members of the reoviridae family and could represent a new genus.

Characterization and molecular mapping of Yr52 for high-temperature adult-plant resistance to stripe rust in spring wheat germplasm PI 183527 - R. S. Ren; M. N. Wang; X. M. Chen; Z. J. Zhang (Theoretical and Applied Genetics, 2012)

Germplasm evaluation and transfer of Verticillium wilt resistance from Pima (Gossypium barbadense) to Upland cotton (G. hirsutum) - Jinfa Zhang; S. Sanogo; R. Flynn; Jit B. Baral; S. Bajaj; S. E. Hughs; Richard G. Percy (Euphytica, 2012)

Negative Effect of High Calcium Levels on Schwann Cell Survival - J.-G. Yan; M. Agresti; L.-L. Zhang; H. S. Matloub; J. R. Sanger (Neurophysiology, 2012)

Drug–Drug Interaction Potential of Marketed Oncology Drugs: In Vitro Assessment of Time-Dependent Cytochrome P450 Inhibition, Reactive Metabolite Formation and Drug–Drug Interaction Prediction - Jane R. Kenny; Sophie Mukadam; Chenghong Zhang; Suzanne Tay; Carol Collins; Aleksandra Galetin; S. Cyrus Khojasteh (Pharmaceutical Research, 2012)

Identification and expression analysis of major histocompatibility complex IIB gene in orange‐spotted grouper Epinephelus coioides - D. Q. Lu; S. B. Yi; M. Yao; Y. W. Li; X. C. Liu; Y. Zhang; H. R. Lin (Journal of Fish Biology, 2012)
In this study, complementary DNA (cDNA) and DNA sequences of major histocompatibility complex (MHC) class IIB genes ( mhcIIB ) were cloned from orange‐spotted grouper Epinephelus coioides . The gene structure of E. coioides mhcIIB consists of five exons and four introns, and its deduced amino acid sequence length is 249 amino acids, including a signal peptide, a peptide‐binding region, an IGC1 domain, a transmembrane region and a cytoplasmic tail. A phylogenetic study showed that E. coioides mhcIIB shared 32·0–79·1% identity with those of other teleosts and mammals. Real‐time reverse transcriptase (RT)‐PCR was performed to detect the class IIB gene expression in eight different tissues. To characterize the relationship between E. coioides mhcIIB gene and pathogens, in vivo and in vitro studies were performed. Challenge of Cryptocaryon irritans revealed that class IIB genes were down‐regulated after 24 and 48 h of challenge, and their expression was later restored at 72 h. Stimulation of isolated E. coioides leukocytes with lipopolysaccharide (LPS) and polyinosinic:polycytidylic acid (PolyI:C) significantly increased peripheral blood and spleen mhcIIB expression, while head kidney mhcIIB expression remained constant.

Erratum to: Production of transgenic tropical maize with cryIAb and cryIAc genes via microprojectile bombardment of immature embryos - N. Bohorova; W. Zhang; P. Julstrom; S. McLean; B. Luna; R. M. Brito; L. Diaz; M. E. Ramos; P. Estanol; M. Pacheco; M. Salgado; D. Hoisington (Theoretical and Applied Genetics, 2012)

Molecular cloning, characterization expression of P450c17-I and P450c17-II and their functions analysis during the reproductive cycle in males of barfin flounder (Verasper moseri) - Guo X. Jin; Hai S. Wen; Feng He; Ji F. Li; Cai F. Chen; Jia R. Zhang; Xiao Y. Chen; Bao Shi; Dan Shi; Yan P. Yang; Bao X. Qi; Na Li (Fish Physiology and Biochemistry, 2012)

Russian wheat aphids ( Diuraphis noxia ) in China: native range expansion or recent introduction? - B. ZHANG; O. R. EDWARDS; L. KANG; S. J. FULLER (Molecular Ecology, 2012)
In this study, we explore the population genetics of the Russian wheat aphid (RWA) ( Diuraphis noxia ), one of the world’s most invasive agricultural pests, in north‐western China. We have analysed the data of 10 microsatellite loci and mitochondrial sequences from 27 populations sampled over 2 years in China. The results confirm that the RWAs are holocyclic in China with high genetic diversity indicating widespread sexual reproduction. Distinct differences in microsatellite genetic diversity and distribution revealed clear geographic isolation between RWA populations in northern and southern Xinjiang, China, with gene flow interrupted across extensive desert regions. Despite frequent grain transportation from north to south in this region, little evidence for RWA translocation as a result of human agricultural activities was found. Consequently, frequent gene flow among northern populations most likely resulted from natural dispersal, potentially facilitated by wind currents. We also found evidence for the long‐term existence and expansion of RWAs in China, despite local opinion that it is an exotic species only present in China since 1975. Our estimated date of RWA expansion throughout China coincides with the debut of wheat domestication and cultivation practices in western Asia in the Holocene. We conclude that western China represents the limit of the far eastern native range of this species. This study is the most comprehensive molecular genetic investigation of the RWA in its native range undertaken to date and provides valuable insights into the history of the association of this aphid with domesticated cereals and wild grasses.

Water sources of urban trees in the Los Angeles metropolitan area - Neeta S. Bijoor; Heather R. McCarthy; Dachun Zhang; Diane E. Pataki (Urban Ecosystems, 2012)

Case report: a p.C618S RET proto-oncogene germline mutation in a large Chinese pedigree with familial medullary thyroid carcinoma - X.-P. Qi; R.-B. Ying; J.-M. Ma; W.-T. Liu; Z.-F. Du; J. Fei; C.-P. Yang; Q.-Z. Song; H.-Y. Jin; Z.-G. Chen; J.-S. Han; J.-Q. Wang; et al. (Familial Cancer, 2012)

Biomimetic tubular nanofiber mesh and platelet rich plasma-mediated delivery of BMP-7 for large bone defect regeneration - A. Berner; J. D. Boerckel; S. Saifzadeh; R. Steck; J. Ren; C. Vaquette; J. Qiyi Zhang; M. Nerlich; R. E. Guldberg; D. W. Hutmacher; M. A. Woodruff (Cell and Tissue Research, 2012)

Molecular diversity of bacteria in Yunnan yellow cattle (Bos taurs) from Nujiang region, China - J. Leng; Y. M. Cheng; C. Y. Zhang; R. J. Zhu; S. L. Yang; X. Gou; W. D. Deng; H. M. Mao (Molecular Biology Reports, 2012)